A version of the projection-iterative method for the solution of Fredholm integral equations of the second kind - Feruk, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We discuss the problem of application of Alpert’s multiwavelets to the solution of Fredholm integral equations by theprojection-iterative method.